A mediated model of the effects of human resource management policies and practices on the intention to promote women: An investigation of the theory of planned behaviour. Issue 9 (15th May 2017) - Biswas, Kumar; Boyle, Brendan; Mitchell, Rebecca; Casimir, Gian
Abstract: This study investigates the role of supportive human resource management policies and practices in senior HR managers' intention to promote women to senior management positions. Based on the theory of planned behaviour, we argue a model in which supportive HR policies and practices affect managers' attitudes towards the promotion of women to senior positions and their perception of organisational norms and control over the decision. We employ partial least squares based structural equation modelling to investigate data from a sample of 183 firms in Bangladesh. Our results support the utility of the theory of planned behaviour in understanding the positive effects of HR practices on the intent of senior managers to promote women. Our findings suggest that the role of HR policies and practices is not only to eliminate opportunity for discrimination but also to encourage the development of deeper attitudinal and normative acceptance of women's role in senior management.